P1 of turnip mosaic virus interacts with NOD19 for vigorous infection - Bello, Esther O.; Yang, Yingshuai; Fang, Yue; Chai, Mengzhu; Jiang, Xue; Luan, Yameng; Wang, Yuting; Guo, Yating; Wu, Xiao-Yun; Cheng, Xiaofei; Wu, Xiao-Xia (Frontiers in Microbiology, 2023)
P1 protein, the most divergent protein of virus members in the genus Potyvirus of the family Potyviridae, is required for robust infection and host adaptation. However, how P1 affects viral proliferation is still largely elusive. In this work, a total number of eight potential P1-interacting Arabidopsis proteins were identified by the yeast-two-hybrid screening using the turnip mosaic virus (TuMV)-encoded P1 protein as the bait. Among which, the stress up-regulated NODULIN 19 (NOD19) was selected for further characterization. The bimolecular fluorescent complementation assay confirmed the interaction between TuMV P1 and NOD19. Expression profile, structure, and subcellular localization analyses showed that NOD19 is a membrane-associated protein expressed mainly in plant aerial parts. Viral infectivity assay showed that the infection of turnip mosaic virus and soybean mosaic virus was attenuated in the null mutant of Arabidopsis NOD19 and NOD19-knockdown soybean seedlings, respectively. Together, these data indicate that NOD19 is a P1-interacting host factor required for robust infection.